Comparison of single versus burst-pulse mode in IPL in patients with acne vulgaris - Atif Shehzad (Journal of Pakistan Association of Dermatologists, 2022)
Background Acne vulgaris is a very frequently occurring disease in adolescence and adulthood. The coalescence of adverse impacts of systemic and topical anti acne treatments, antimicrobial resistance and inclination for high tech strategies has led to a new interest in light based acne treatment. Intense pulsed light (IPL) has been utilized to treat facial acne. Data on local population is not available that compares single versus burst-pulse mode in IPL in acne vulgaris patients. Objective To compare the outcomes of single versus burst-pulse mode in IPL in patients having acne vulgaris. Methods A Randomized controlled trail was conducted at the Department of dermatology, Sir Ganga Ram Hospital Lahore. 300 Patients were randomly split up into two groups (150 each). In group-A burst-pulse mode was used to treat the patients, and in group-B the patients were managed with single-pulse mode. Forearm was selected to apply the test dose with IPL, and the most endurable dosage was chosen. Acne global severity scale was calculated at baseline and after completion of four sessions. Percentage improvement in acne global severity scale was calculated. Results The mean age of cases was 29.86±9.62 years. Overall there were 72(24%) male and 228(76%) female cases. The mean Acne global severity scale at baseline was 3.10±0.83 in Single pulse mode and 3.07±0.87 in Burst-pulse mode with no significant difference. The mean Acne global severity scale at 4th week was 1.58±0.50 and 1.39±0.75 with significantly lower score and Burst-Pulse mode, p-value < 0.05. The mean percentage improvement in single pulse mode was 49.56±16.41% and in Burst-Pulse mode was 63±18.98 %. The mean percentage improvement in Burst –pulse mode was significantly higher than single pulse mode, p-value < 0.001. Conclusion As per findings of the study, it is concluded that at 4th week percentage improvement was significantly higher in burst-pulse mode in IPL as compared to single-pulse mode in patients with acne vulgaris. So, using Burst-pulse mode can achieve early recovery and can reduce the severity of the disease. Combining IPL with systemic and topical medications can improve the effectiveness of this treatment.